1994
DOI: 10.1128/mcb.14.6.4193
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibition causes morphological reversion of ras-transformed cells by a complex mechanism that involves regulation of the actin cytoskeleton.

Abstract: A potent and specific small molecule inhibitor of farnesyl-protein transferase, L-739,749, caused rapid morphological reversion and growth inhibition of ras-transformed fibroblasts (Ratl/ras cells). Morphological reversion occurred within 18 h of L-739,749 addition. The reverted phenotype was stable for several days in the absence of inhibitor before the transformed phenotype reappeared. Cell enlargement and actin stress fiber formation accompanied treatment of both Ratl/ras and normal Ratl cells. Significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
170
3
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 18 publications
14
170
3
1
Order By: Relevance
“…This is consistent with previous reports by Prendergast et al (1994), and SeppLorenzino et al (1995). In Colo357, A-549 and Calu-1 cells, K-Ras prenylation is inhibited only by cotreatment with FTI-277 and GGTI-298.…”
Section: Inhibition Of Soft Agar Does Not Require Inhibition Of Oncogsupporting
confidence: 94%
“…This is consistent with previous reports by Prendergast et al (1994), and SeppLorenzino et al (1995). In Colo357, A-549 and Calu-1 cells, K-Ras prenylation is inhibited only by cotreatment with FTI-277 and GGTI-298.…”
Section: Inhibition Of Soft Agar Does Not Require Inhibition Of Oncogsupporting
confidence: 94%
“…Furthermore, our soft agar results are consistent with those of Sepp-Lorenzino et al (1995) who showed that the ability of FTase inhibitors to inhibit human tumor cell line growth in soft agar does not correlate with their Ras mutation status. In addition, others have demonstrated that the ability of FTase inhibitors to reverse morphological transformation did not correlate with their ability to inhibit Ras prenylation (Prendergast et al, 1994). Taken together these results suggest that farnesylated protein(s) other than oncogenic K-Ras, that are pivotal to transformation, are targets for FTase inhibitors.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, CAAX peptidomimetics inhibited the anchorage-dependent growth of ras-transformed cells but had little e ect on the growth of normal cells (Kohl et al, 1993;James et al, 1993). However, the ability of FTase inhibitors to reverse morphological transformation was shown not to correlate with their ability to inhibit Ras prenylation (Prendergast et al, 1994), and the Ras mutation status did not predict the sensitivity of human tumor cell growth in soft agar (SeppLorenzino et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Candidates that could ful®ll this role are a family of protein tyrosine phosphatases (PRL1) with oncogenic properties, an inositol phosphatase and members of the Ras-like superfamily, like RhoB, RhoE, Rheb. In fact, Prendergast and others have proposed that RhoB might be the target responsible for changes in morphologic transformation induced by the FTI 43,44,47,48 as was observed in TSU-Pr1 cells.…”
Section: Discussionmentioning
confidence: 93%